Analisis Iklim Sekolah dan Persepsi Keadilan Organisasional terhadap Keterlibatan Profesional Guru - Andi Tyas Pambudi; Gariyanto Gariyanto; Agus Sutanto (Journal of Education and Teaching Learning, 2026)
This article aims to systematically synthesize recent literature on school climate and organizational justice as organizational foundations for strengthening teacher professionalism. The study employed a Systematic Literature Review (SLR) with PRISMA-informed stages, including identification, screening, eligibility assessment, data extraction, quality appraisal, and thematic synthesis. Twenty-five publications from 2021 to 2026 were reviewed because they discussed school climate, organizational climate, organizational justice, leadership, job satisfaction, commitment, professional development, performance, and teacher professionalism. The findings show that teacher professionalism is shaped not only by individual competence but also by the organizational environment. A positive school climate provides psychological safety, collegial collaboration, open communication, academic support, and professional learning opportunities. Organizational justice strengthens these conditions through proportional workload distribution, transparent procedures, respectful interaction, equitable development access, and fair recognition. The novelty of this article lies in integrating school climate and organizational justice into a single conceptual framework. The synthesis shows that supportive and fair leadership, positive climate, justice, and continuous professional development strengthen teacher commitment, motivation, satisfaction, engagement, and instructional quality. The article recommends participatory governance, transparent workload management, academic supervision, professional learning communities, and fair recognition systems.